Coated film structure, coating composition, and building material
By adding photocatalyst particles and porous surfaces to the photocatalytic layer and using ring or chain siliconica particles, the problem of insufficient photocatalytic action of the photocatalytic layer in the prior art is solved, and stronger anti-fouling performance and more effective decomposition of organic pollutants are achieved.
Patent Information
- Application Number
- JP2023179863
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-18
- Publication Date
- 2025-05-01
AI Technical Summary
The prior art is difficult to effectively utilize the photocatalytic action of the photocatalytic layer, resulting in insufficient antifouling performance.
A photocatalytic layer containing photocatalyst particles is used, with one side of the photocatalytic layer being a porous surface to increase the surface area, and annular or chain silicone particles are added to the photocatalytic layer to regulate the photocatalytic action.
The photocatalytic effect of the photocatalytic layer is improved, and the anti-fouling properties are enhanced, so that building materials can more effectively decompose organic pollutants under light, and improve the cleanliness and durability of the surface.
Smart Images

Figure 2025069874000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating film construction, a coating composition, and a building material. More specifically, the present invention relates to a coating film construction, a coating composition capable of producing the coating film construction, and a building material comprising the coating film construction. [Background technology]
[0002] In Patent Document 1, (a)(R 1 ) n Si(OR 2 ) 4-n (R 1 When two are present, they may be the same or different and represent a monovalent organic group having 1 to 8 carbon atoms; R 2 The present invention discloses a coating composition for undercoating a photocatalyst-containing coating film, which comprises at least one organosilane represented by the formula (I) (wherein n is an integer of 0 to 2 and n is the same or different, and represents an alkyl group having 1 to 5 carbon atoms or an acyl group having 1 to 6 carbon atoms), the average value of n being less than 1, at least one selected from the group consisting of a mixture of organosilanes, a hydrolysate of the mixture, and a condensate of the mixture, and (b) an organic-inorganic hybrid polymer prepared by adding (c) a hydrolysis / condensation catalyst, and (d) water to a polymer containing a silyl group having a silicon atom bonded to a hydrolyzable group and / or a hydroxyl group, and in which the weight ratio of component (a) (calculated as a completely hydrolyzed condensate) / component (b) is 5 / 95 to 40 / 60. Patent Document 1 discloses that the coating composition for undercoating can prevent deterioration of a substrate caused by a photocatalyst, can provide a coating film having high hardness, excellent weather resistance, and excellent long-term durability and adhesion, and can be suitably used as an undercoat for a photocatalyst-containing coating film. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-113063 A Summary of the Invention [Problem to be solved by the invention]
[0004] If the photocatalytic action of the layer containing the photocatalyst as described in Patent Document 1 can be enhanced, improvement in antifouling properties can be expected.
[0005] The present invention has been made in consideration of the above-mentioned reasons, and aims to provide a coating film structure capable of efficiently exerting the photocatalytic action of a photocatalyst layer, a coating composition capable of producing a photocatalyst layer provided in the coating film structure, and a building material provided with the coating film structure. [Means for solving the problem]
[0006] The coating film construction of the present invention includes a photocatalyst layer containing a binder and photocatalyst particles dispersed in the binder. One of two surfaces of the photocatalyst layer facing opposite directions is a porous surface having a plurality of pores communicating with the outside of the photocatalyst layer.
[0007] The coating composition of the present invention contains a binder raw material, photocatalyst particles, and inorganic particles, and the inorganic particles contain at least one of chain particles and ring particles.
[0008] The building material of the present invention comprises a substrate and the coating film structure. Effect of the Invention
[0009] According to the present invention, it is possible to provide a coating film construction capable of efficiently exerting the photocatalytic action of a photocatalyst layer, a coating composition capable of producing a photocatalyst layer provided in the coating film construction, and a building material provided with the coating film construction. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a coating film structure according to one embodiment of the present invention. [Diagram 2] 2A and 2B are schematic cross-sectional views showing examples of a coating film structure according to one embodiment of the present invention. [Diagram 3]FIG. 3 is a cross-sectional SEM image obtained by observing a part of the cross section of the evaluation sample of Example 1 with a scanning electron microscope (SEM). [Figure 4] FIG. 4 is a cross-sectional SEM image obtained by observing a part of the cross section of the evaluation sample of Comparative Example 1 with a scanning electron microscope (SEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Embodiment] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that each drawing is a schematic drawing, and the size of each component in the drawing does not necessarily reflect the actual size.
[0012] 1. Overview The coating film construction 1 of the present invention includes a photocatalyst layer 2 containing a binder 24 and photocatalyst particles 20 dispersed in the binder 24. One of the two surfaces of the photocatalyst layer 2 facing opposite directions is a porous surface 25 having a plurality of pores 251 leading to the outside of the photocatalyst layer 2. The above-mentioned configuration allows the photocatalytic action of the photocatalyst layer 2 to be efficiently exerted. The reason for the above-mentioned effect is not necessarily clear, but can be inferred as follows, for example. The photocatalyst layer 2 has a porous surface 25 having pores 251, and therefore the surface area of the photocatalyst layer 2 can be increased. This allows the photocatalyst particles 20 with enhanced catalytic activity to be efficiently increased, and as a result, the photocatalytic action of the photocatalyst layer 2 can be efficiently exerted. The photocatalytic action of the photocatalyst layer 2 refers to the action of decomposing nearby organic matter by active species generated from the surface of the photocatalyst particles 20.
[0013] The coating film construction 1, which can efficiently exert the photocatalytic action of the photocatalyst layer 2, can improve its antifouling properties. Therefore, the coating film construction 1 is suitably used for producing building materials that require antifouling properties. In other words, a building material in which the coating film construction 1 is disposed on the surface of a substrate can exhibit high antifouling properties.
[0014] 2. Coating film composition 1 is a cross-sectional view of a coating film construction 1 of this embodiment. The coating film construction 1 includes a coating film layer 3 and a photocatalyst layer 2 disposed so as to be in contact with the coating film layer 3. The photocatalyst layer 2 contains photocatalyst particles 20. In this embodiment, the coating film layer 3 is composed of an undercoat layer 32 and a topcoat layer 31. In producing the coating film construction 1, for example, the undercoat layer 32, the topcoat layer 31, and the photocatalyst layer 2 are produced in this order on a substrate or the like.
[0015] (Photocatalyst layer) The structure, characteristics, etc. of the photocatalyst layer 2 will now be described in detail.
[0016] The thickness of the photocatalyst layer 2 is not particularly limited, but the thicker it is, the more the photocatalytic action of the photocatalyst layer 2 can be improved. However, if the thickness exceeds 1.0 μm, the photocatalytic action of the photocatalyst layer 2 tends to remain almost unchanged. In addition, if the thickness is 0.2 μm or more, the photocatalytic action of the photocatalyst layer 2 can be improved, and therefore, the thickness is usually preferably in the range of 0.2 μm to 1.0 μm, and more preferably in the range of 0.2 μm to 0.8 μm. The thickness of the photocatalyst layer 2 can be confirmed as follows. First, the coating film construction 1 is cut to obtain a slice in which the cross section of the coating film construction 1 is exposed. Then, the length of the photocatalyst layer 2 in the cross section is measured. A specific method for measuring the length in the cross section is a method using a scanning electron microscope (SEM). Therefore, the length in the cross section is measured at multiple points (for example, any 10 points) of the photocatalyst layer 2 using SEM, and the arithmetic average value of the measurement results at the multiple points can be the thickness of the photocatalyst layer 2.
[0017] The photocatalyst layer 2 has a porous surface 25. As described above, one of the two surfaces of the photocatalyst layer 2 facing opposite to each other is the porous surface 25. In this embodiment, the photocatalyst layer 2 has a front surface 21 and a back surface 22 facing opposite to each other, and the front surface 21 is the porous surface 25. In other words, it is preferable that the surface exposed to the outside is the porous surface 25, and in this embodiment, the surface exposed to the outside is the porous surface 25, and this surface is defined as the front surface 21. In addition, the surface of the photocatalyst layer 2 that is opposite to the front surface 21 and in contact with the coating layer 3 is defined as the back surface 22. In addition, the porous surface 25 has a plurality of pores 251 that communicate with the outside of the photocatalyst layer 2. The size and shape of the plurality of pores 251 are not particularly limited. In addition, the size of the pores 251 may not be uniform, and the shape may not be uniform. In other words, the porous surface 25 may have pores 251 having various sizes and shapes.
[0018] In addition, it is preferable that the porous surface 25 of the photocatalyst layer 2 has a suitable roughness, and in this case, the surface area of the porous surface 25 of the photocatalyst layer 2 can be suitably increased. This makes it possible to increase the photocatalyst particles 20 whose catalytic activity is enhanced when the photocatalyst layer 2 is irradiated with light. Specifically, the roughness of the porous surface 25 is preferably 20 nm or more, and more preferably 50 nm or more. The roughness of the porous surface 25 is preferably 200 nm or less, and more preferably 100 nm or less. The roughness of the porous surface 25 of the photocatalyst layer 2 is the arithmetic mean roughness (Ra), and can be measured using an atomic force microscope (AFM) or the like.
[0019] Furthermore, it is preferable that the photocatalyst layer 2 is made moderately porous, and specifically, it is preferable that the area occupied by the portions where the pores 251 exist in the cross section of the photocatalyst layer 2 (hereinafter, also referred to as porosity) is in the range of 1% to 20%. If the porosity is 1% or more, the photocatalytic activity of the photocatalyst layer 2 can be sufficiently enhanced. If the porosity is 20% or less, peeling between the photocatalyst layer 2 and the coating layer 3 can be suppressed. It is more preferable that the porosity is 3% or more. It is more preferable that the porosity is 10% or less.
[0020] In this way, by setting the thickness of the photocatalyst layer 2, the roughness of the porous surface 25, or the porosity in the photocatalyst layer 2 to a specific range, the photocatalytic action of the photocatalyst layer 2 can be improved, and more substances can be decomposed by the photocatalytic action of the photocatalyst layer 2. The decomposed substances can be washed away with water, etc., and in this case, it is preferable to adjust the water contact angle of the porous surface 25 of the photocatalyst layer 2 to a range of 50° or less. In this case, the photocatalyst layer 2 can have appropriate hydrophilicity, so that the decomposed substances can be easily washed away.
[0021] Next, the components contained in the photocatalyst layer 2 will be described in detail.
[0022] The photocatalyst layer 2 contains a binder 24. Examples of the binder 24 include siloxane-based resins. The siloxane-based resin is a resin having a siloxane bond (Si-O-Si) in the molecule, and includes at least one reaction product of an organosilicon compound and its hydrolysis condensate. Examples of the organosilicon compound include alkoxysilane, silazane, and oligomers using these as raw materials. The alkoxysilane is represented by, for example, formula (1).
[0023] (R 1 ) n Si(OR 2 ) 4-n ...(1)
[0024] n can be 1 or 2.
[0025] R in formula (1) 1Examples of the functional group include an alkyl group, a cycloalkyl group, an aryl group, and a vinyl group. The alkyl group may be linear or branched. Examples of such an alkyl group include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, an s-butyl group, an t-butyl group, a pentyl group, a hexyl group, a heptyl group, and an octyl group. Examples of the cycloalkyl group include a cyclohexyl group, a cycloheptyl group, and a cyclooctyl group. Examples of the aryl group include a phenyl group. Each of the above functional groups may have an arbitrary substituent. Examples of such a substituent include a halogen atom, a (meth)acryloyl group, a mercapto group, and an alicyclic group. R in formula (1) 2 The alkyl group represented by the formula (I) may be linear or branched, and examples of such an alkyl group include a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an i-butyl group, an s-butyl group, a t-butyl group, and a pentyl group.
[0026] Specific examples of the organosilicon compound represented by formula (1) include, for example, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, i-propyltrimethoxysilane, i-propyltriethoxysilane, γ-chloropropyltrimethoxysilane, γ-chloropropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 3,3,3-trifluoropropyltrimethoxysilane, 3,3,3-trifluoropropyltriethoxysilane, Examples of the organic silicon compounds include silane, cyclohexyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, methylphenyldimethoxysilane, dimethyldipropoxysilane, etc. These organic silicon compounds can be used alone or in combination of two or more. Specific examples of hydrolysis condensates of organosilicon compounds include commercially available products such as KR-211, KR-212, KR-213, KR-214, KR-216, and KR-218 manufactured by Shin-Etsu Chemical Co., Ltd., and TSR-145, TSR-160, TSR-165, and YR-3187 manufactured by Toshiba Silicones.
[0027] The binder 24 may contain the organosilicon compound itself.
[0028] The photocatalyst layer 2 contains photocatalyst particles 20. As described above, when the photocatalyst particles 20 are irradiated with light, the photocatalyst particles 20 can be excited. This enhances catalytic activity, and as a result, the photocatalyst layer 2 can exert a photocatalytic effect. For example, the ratio of the photocatalyst particles 20 to the entire photocatalyst layer 2 is 5% by mass or more and 60% by mass or less. In this case, the photocatalytic effect of the photocatalyst layer 2 can be exerted more efficiently. This ratio is preferably 20% by mass or more. This ratio is preferably 40% by mass or less.
[0029] In this embodiment, the photocatalyst particles 20 contain titanium oxide particles. The titanium oxide particles have high catalytic activity. Therefore, the photocatalytic action of the photocatalyst layer 2 can be exhibited more efficiently.
[0030] Examples of the form of titanium oxide include rutile, anatase, and brookite types, and among these, rutile is particularly preferred. In other words, it is particularly preferred that the photocatalyst particles 20 contain rutile titanium oxide particles.
[0031] The reason why the photocatalyst particles 20 are particularly preferably made to contain rutile-type titanium oxide particles will be described in detail. In the present invention, the photocatalyst layer 2 has a porous surface 25, but due to the structure of the porous surface 25, the photocatalyst layer 2 can efficiently exhibit its photocatalytic action even without using a material whose catalytic activity is excessively high. In other words, since the photocatalyst layer 2 has a porous surface 25, the photocatalytic action of the photocatalyst layer 2 can be maintained even if a material whose catalytic activity is moderately suppressed, such as rutile-type titanium oxide particles, is applied. On the other hand, since a material whose catalytic activity is moderately suppressed, such as rutile-type titanium oxide particles, can be applied to the photocatalyst layer 2, the photocatalytic action of the photocatalyst layer 2 at a location farther away from the porous surface 25 can be suppressed. This can suppress peeling between the photocatalyst layer 2 and the coating layer 3 due to deterioration of the coating layer 3. For these reasons, the photocatalyst particles 20 are particularly preferably made to contain rutile-type titanium oxide particles.
[0032] In addition, the titanium oxide particles are not limited to rutile type titanium oxide particles, and in order to efficiently exert the photocatalytic action of the photocatalyst layer 2, at least one of rutile type titanium oxide particles, anatase type titanium oxide particles, and brookite type titanium oxide particles can be used in combination.
[0033] The average particle diameter of the photocatalyst particles 20 is, for example, 5 nm or more and 200 nm or less. In this case, the dispersibility of the photocatalyst particles 20 in the binder 24 can be improved. This makes it possible to adjust the photocatalytic action of the photocatalyst layer 2. The average particle diameter is preferably 10 nm or more. The average particle diameter is preferably 100 nm or less. The average particle diameter of the photocatalyst particles 20 refers to the arithmetic mean value of the maximum diameters of a plurality of particles (for example, any 50 particles) measured using a scanning electron microscope (SEM).
[0034] Next, in this embodiment, the photocatalyst layer 2 contains inorganic particles 27. By containing the inorganic particles 27 in the photocatalyst layer 2, the photocatalytic action of the photocatalyst layer 2 can be adjusted. For example, by increasing the ratio of the inorganic particles 27 in the photocatalyst layer 2, the photocatalytic action can be appropriately suppressed, and by decreasing the ratio of the inorganic particles 27 in the photocatalyst layer 2, the photocatalytic action can be appropriately improved. The mass ratio of the photocatalyst particles 20 and the inorganic particles 27 in the photocatalyst layer 2 is not particularly limited, but if it is within the range of, for example, 20:80 to 50:50, the photocatalytic action of the photocatalyst layer 2 can be easily adjusted.
[0035] Furthermore, when the inorganic particles 27 contain silica, the photocatalytic activity of the photocatalyst layer 2 can be more easily adjusted, and therefore in this embodiment, the inorganic particles 27 contain silica.
[0036] The photocatalyst layer 2 preferably has a concentration gradient such that the concentration of the photocatalyst particles 20 decreases with increasing distance from the porous surface 25. In this case, the photocatalytic action of the photocatalyst layer 2 disposed at a location farther from the porous surface 25 can be suppressed. The concentration gradient of the photocatalyst particles 20 in the photocatalyst layer 2 can be confirmed by the following method. First, a slice is obtained in which the cross section of the coating film construction 1 is exposed. Next, the cross section of the coating film construction 1 in the slice is polished by an ion beam in the direction perpendicular to the cross section via a shielding plate. At this time, a cover glass is interposed in the gap between the shielding plate and the uneven coating film construction 1, and the shielding plate and the coating film construction 1 are adhered to each other with a highly heat-dissipating adhesive. Then, the coating film construction 1 is exposed by being slightly shifted from the shielding plate, and the exposed portion is irradiated with an ion beam to perform polishing. The cross section obtained by processing in this manner can maintain a state in which the fine composition in the photocatalyst layer 2 is not destroyed. Therefore, the location where the photocatalyst particles 20 are arranged in the photocatalyst layer 2 can be accurately grasped. By observing this cross section using an SEM, the concentration gradient of the photocatalyst particles 20 in the photocatalyst layer 2 can be confirmed.
[0037] (Coating Composition) The method for forming the photocatalyst layer 2 is not particularly limited, but in this embodiment, the photocatalyst layer 2 is produced by applying a coating composition (X) containing a binder raw material, photocatalyst particles 20, and inorganic particles 27.
[0038] The binder 24 contained in the photocatalyst layer 2 is formed from a binder raw material. The binder raw material contains, for example, the above-mentioned organosilicon compound and its hydrolysis condensate. The binder raw material may contain at least one reaction product of the organosilicon compound and its hydrolysis condensate, that is, a siloxane resin.
[0039] As described above, in this embodiment, the inorganic particles 27 contained in the photocatalyst layer 2 contain silica, and therefore the inorganic particles 27 contained in the coating composition (X) also contain silica. The form of the silica contained in the coating composition (X) is preferably colloidal, and more specifically, colloidal silica dispersed in an aqueous medium is preferably used.
[0040] In addition, the inorganic particles 27 contained in the coating composition (X) contain particles having various shapes. For example, the inorganic particles 27 contain at least one type selected from the group consisting of spherical inorganic particles, inorganic particles in which a plurality of spherical inorganic particles are linked together to form a chain (hereinafter, chain particles), and inorganic particles in which a plurality of spherical inorganic particles are linked together to form a ring (hereinafter, ring particles). In addition, the inorganic particles 27 preferably contain at least one of chain particles and ring particles. In other words, the inorganic particles 27 contained in the coating composition (X) preferably contain at least one of chain particles and ring particles. In this case, light can more easily reach the inside of the photocatalyst layer 2, and the photocatalyst particles 20 with enhanced catalytic activity can be further increased.
[0041] The average particle size of the spherical inorganic particles is preferably 5 nm to 100 nm. The size and shape of the chain particles are not particularly limited, but it is preferable that the chain particles are formed by connecting spherical inorganic particles having an average particle size of 5 nm to 100 nm, and more preferably, the thickness of the chain particles is 5 nm to 50 nm and the length is 50 nm to 400 nm. The size and shape of the ring particles are not particularly limited, but it is preferable that the ring particles are formed by connecting spherical inorganic particles having an average particle size of 5 nm to 100 nm, and more preferably, the length of the ring particles is 50 nm to 400 nm.
[0042] In addition, the photocatalyst layer 2 preferably has a concentration gradient in which the concentration of the photocatalyst particles 20 decreases as the distance from the porous surface 25 increases, in other words, as the distance increases from the front surface 21 to the rear surface 22. However, when the inorganic particles 27 contain at least one of chain particles and ring particles, the above-mentioned concentration gradient is more likely to be obtained. Although the reason is not clear, it is presumed to be due to the following mechanism. For example, when the inorganic particles 27 do not contain chain particles or ring particles, the inorganic particles 27 in the photocatalyst layer 2 tend to be packed closely together, and the photocatalyst particles 20 tend to be evenly arranged throughout the photocatalyst layer 2 (see FIG. 2A). In contrast, chain particles or ring particles tend to be easily settled due to large steric hindrance, and therefore tend to be arranged on the rear surface 22. When such chain particles or ring particles with large steric hindrance are arranged on the rear surface 22 side, the rear surface 22 is raised, and the concentration of the photocatalyst particles 20 near the rear surface 22 tends to decrease (see FIG. 2B). It is presumed that, due to such a mechanism, when at least one of chain particles and cyclic particles is contained, the photocatalyst layer 2 is more likely to have a concentration gradient in which the concentration of the photocatalyst particles 20 decreases from the front surface 21 to the back surface 22. In addition, the sawtooth-shaped portion near the front surface 21 in Figures 2A and 2B indicates that the substance attached to the photocatalyst layer 2 is decomposed by the photocatalytic action of the photocatalyst layer 2, but when the photocatalyst layer 2 has a concentration gradient in which the concentration of the photocatalyst particles 20 decreases from the front surface 21 to the back surface 22, the proportion of the photocatalyst particles 20 near the front surface 21 is increased, so that the photocatalytic action of the photocatalyst layer 2 near the front surface 21 can be further improved. The sawtooth-shaped areas near the back surface 22 in Figures 2A and 2B indicate that deterioration of the coating layer 3 has occurred due to the photocatalytic action of the photocatalytic layer 2. However, since the proportion of photocatalytic particles 20 near the back surface 22 is reduced, the photocatalytic action of the photocatalytic layer 2 near the back surface 22 can be suppressed, and as a result, peeling between the photocatalytic layer 2 and the coating layer 3 due to deterioration of the coating layer 3 can be further suppressed (see Figure 2).
[0043] The coating composition (X) may also contain a solvent. The inclusion of a solvent can increase the ease of application of the coating composition (X). The type of solvent is not particularly limited, but it is preferable to select a solvent that allows the applied coating composition (X) to be appropriately dried. In this embodiment, the coating composition (X) is applied by spraying using a spray application method, as will be described in detail later. However, it is also preferable to adjust the viscosity of the coating composition (X) using a solvent so that the coating composition (X) has a viscosity that can be applied by spraying.
[0044] (Method of forming photocatalyst layer) Next, a method for applying the above-mentioned coating composition (X) to form the photocatalyst layer 2 will be described. First, the coating composition (X) is applied onto the pre-formed coating layer 3. As described above, in this embodiment, the coating composition (X) is applied by a spray application method. By employing this method, a porous surface 25 can be formed on the photocatalyst layer 2. The conditions of the spray application method can be appropriately adjusted so that the porous surface 25 is formed.
[0045] More specifically, when adopting the spray coating method, a method of applying the coating composition (X) by spraying it using an air spray device can be mentioned. The type of the air spray device is not particularly limited, and a fixed air spray device or a small air spray device such as a hand spray gun may be used. In addition, the discharge pressure of the air spray device is not particularly limited, but it is preferably performed at 0.05 MPa or more and 0.30 MPa or less. By adjusting the discharge pressure of the air spray device, the particle size of the coating composition (X) to be applied can be adjusted. This allows the ease of drying of the applied coating composition (X) to be adjusted. When the coating composition (X) is appropriately easy to dry, the photocatalyst particles 20 are less likely to settle, and as a result, it is easy to generate a concentration gradient in which the concentration of the photocatalyst particles 20 decreases as it approaches the back surface 22 from the front surface 21. In addition, the particle size of the coating composition (X) when applied is preferably adjusted to 2 mm or less, more preferably 1 mm or less, from the viewpoint of drying property.
[0046] Subsequently, the applied coating composition (X) is dried to remove the solvent. The drying conditions are not particularly limited, but for example, the coating composition (X) can be dried without heating or the like by adjusting the particle size when spraying the coating composition (X) to within the above range. Depending on the components contained in the coating composition (X), the applied coating composition (X) may be heated to remove the solvent.
[0047] In this way, the photocatalyst layer 2 can be formed by applying and drying the coating composition (X). In the process of forming the photocatalyst layer 2 from the coating composition (X), the coating composition (X) gradually loses fluidity and approaches a cured state. Therefore, in other words, the photocatalyst layer 2 contains a cured product of the coating composition (X).
[0048] (Coating layer) As described above, the coating film structure 1 includes the coating film layer 3 arranged so as to be in contact with the photocatalyst layer 2 (see FIG. 1). The coating film layer 3 is composed of an undercoat layer 32 and an overcoat layer 31 arranged on the undercoat layer 32.
[0049] The topcoat layer 31 contains an organic-inorganic composite. In this case, the weather resistance of the coating film structure 1 can be improved. The organic-inorganic composite is a material in which an organic component and an inorganic component are composited, and in particular, a material in which an organic component and an inorganic component are chemically bonded. The organic-inorganic composite contains at least one reaction product of an organosilicon compound and its hydrolysis condensate, that is, a siloxane resin, similar to the binder 24, for example.
[0050] Moreover, the topcoat layer 31 is formed by applying a coating agent (hereinafter also referred to as an organic-inorganic composite resin-containing paint) for forming the topcoat layer 31. To explain by giving a specific example, the organic-inorganic composite resin-containing paint contains the following components (A) to (C), and the components (A) to (C) can react with each other to produce an organic-inorganic composite.
[0051] Component (A): A water dispersion of an organic-inorganic composite resin obtained by neutralizing a hydrolysis condensation reaction product of components (a) and (b) with a neutralizing agent and adding water. Component (a): Organosilicon compound or its hydrolysis condensate Component (b): a silyl group-containing vinyl resin having a hydrolyzable silyl group or a silyl group having a silicon atom bonded to a hydroxyl group. Component (B): Alkoxysilane having an amino group capable of hydrolytic condensation reaction Component (C): A compound having an epoxy group in the molecule that is reactive with the amino group of component (B)
[0052] For example, the organosilicon compound or its hydrolysis condensate contained in component (a) may be the same as the organosilicon compound or its hydrolysis condensate contained in coating composition (X).
[0053] The component (b) may be a silyl group-containing vinyl resin. The silyl group-containing vinyl resin has at least one, preferably two or more, hydrolyzable silyl groups or silyl groups having silicon atoms bonded to hydroxyl groups at the end or side chain of the resin per molecule. The acid value of the silyl group-containing vinyl resin is, for example, 20 to 150 mgKOH / g. The number average molecular weight of the silyl group-containing vinyl resin is, for example, 1,000 to 50,000.
[0054] The silyl group contained in the silyl group-containing vinyl resin is represented by the formula (2).
[0055] -SiX m (R 3 ) 3-m ...(2)
[0056] Examples of X include hydrolyzable groups such as alkoxy groups, acyloxy groups, halogen groups, ketoximate groups, mercapto groups, alkenyloxy groups, and phenoxy groups, and hydroxyl groups. 3 Examples of the group include hydrogen or monovalent hydrocarbon groups such as alkyl groups, aryl groups, and aralkyl groups having 1 to 10 carbon atoms.
[0057] The silyl group-containing vinyl resin can be produced, for example, by reacting a hydrosilane compound represented by the formula (3) with a vinyl resin having a carbon-carbon double bond.
[0058] H-SiX m (R 3 ) 3-m ...(3)
[0059] In formula (3), X and R 3 and m may each be the same as in formula (2).
[0060] Examples of the hydrosilane compound include methyldichlorohydrosilane, methyldiethoxyhydrosilane, and methyldiacetoxyhydrosilane.
[0061] Examples of monomers constituting vinyl resins include carboxylic acids such as (meth)acrylic acid, itaconic acid, and fumaric acid, and acid anhydrides such as maleic anhydride.
[0062] Next, a method for producing an aqueous dispersion of an organic-inorganic composite resin, which is component (A), will be described. First, a hydrolysis-condensation reaction product is produced by hydrolysis and condensation reaction in the presence of water and a catalyst in a mixture of the above-mentioned components (a) and (b). Examples of the catalyst to be added to the mixture of components (a) and (b) include inorganic acids such as nitric acid and hydrochloric acid, and organic acids such as acetic acid, formic acid, and propionic acid. The hydrolysis-condensation reaction product is in a solution state due to the alcohol content produced by the reaction, or due to the alcohol content and an organic solvent added as necessary.
[0063] Next, a neutralizing agent is added to the solution of the hydrolysis condensation reaction product thus obtained, and the solution is uniformly dispersed. After neutralization, water is added, or the neutralizing agent and water are added simultaneously, and the mixture is stirred to forcibly disperse the mixture, thereby obtaining an aqueous dispersion (emulsion). The amount of water added after neutralization is determined arbitrarily, taking into consideration the coating workability of the paint, etc. In this way, an aqueous dispersion of an organic-inorganic composite resin can be obtained.
[0064] The component (B) is an alkoxysilane capable of undergoing a hydrolytic condensation reaction and having an amino group in the molecule. Specifically, an amino group-containing alkoxysilane represented by the formula (4) can be suitably used.
[0065] (R 6 -NH-R 5 -) n Si(OR 4 ) 4-n ...(4)
[0066] R 4 Examples of R include alkyl groups having 1 to 5 carbon atoms. 5 Examples of R include alkylene groups having 1 to 5 carbon atoms. 6Examples of the alkyl group include a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, a cycloalkyl group having 5 to 8 carbon atoms, an aryl group having 6 to 8 carbon atoms, a substituted or unsubstituted amino group, etc. n may be an integer of 1 or 2.
[0067] In addition, R 4 The alkyl group as R may be linear or branched, and examples thereof include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, and pentyl groups. Preferred alkyl groups have 1 to 2 carbon atoms. 5 The alkylene group as R may be linear or branched, and examples thereof include a methylene group, an ethylene group, and a propylene group. 6 The alkyl group is R 4 Also, R 6 Examples of the cycloalkyl group as R include a cyclohexyl group and a cycloheptyl group. 6 Examples of the aryl group as R include a phenyl group. 6 Examples of the amino group as the substituent include an amino group in which one or both of the hydrogen atoms have been substituted with an alkyl group having 1 to 5 carbon atoms.
[0068] Examples of the amino group-containing alkoxysilane represented by formula (4) include γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldiethoxysilane, N-cyclohexyl-γ-aminopropyltrimethoxysilane, N-cyclohexyl-γ-aminopropyltriethoxysilane, γ-(2-aminoethyl)-aminopropyltrimethoxysilane, γ-(2-aminoethyl)-aminopropylmethyldimethoxysilane, and γ-anilinopropyltrimethoxysilane.
[0069] The component (C) is a compound having an epoxy group in the molecule that is reactive with the amino group in the component (B). Examples of such compounds include epoxy group-containing alkoxysilanes, alkyl glycidyl ethers and esters, cycloepoxy compounds, bisphenol AF-based low molecular weight epoxy resins, and emulsions of these compounds. Specific examples include γ-glycidoxypropyl trimethoxysilane, γ-glycidoxypropyl triethoxysilane, γ-glycidoxypropyl methyl dimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, γ-glycidoxypropyl triisopropenyloxysilane, γ-glycidoxypropyl triiminoxysilane, β-(3,4-epoxycyclohexyl)ethylmethyl dimethoxysilane, an adduct of γ-isocyanatopropyl triisopropenyloxysilane and glycidol, butyl glycidyl ether, polyoxyethylene glycidyl ether, Cardurer E (product name manufactured by Shell), butylphenyl glycidyl ether, Epicoat 815, 828, 834 (product names manufactured by Yuka Shell Epoxy Co., Ltd.), and emulsions thereof.
[0070] The organic-inorganic composite resin-containing paint can be obtained by mixing the above components (A) to (C) in an appropriate manner, and the obtained organic-inorganic composite resin-containing paint can be applied in an appropriate manner and heated to form the topcoat layer 31. In addition, the organic-inorganic composite resin-containing paint may contain water, an organic solvent, a filler, a dye, a hardening accelerator, a thickener, or a pigment dispersant, etc., as necessary, for the purpose of improving the storage stability and coating workability of the paint composition. For example, as the filler, a normal inorganic or organic dye pigment can be used. Specific examples include titanium oxide, pearl mica, zinc sulfide, zinc white, white lead, lithopone, carbon black, lamp black, iron blue, phthalocyanine blue, ultramarine, carmine FB, yellow lead, zinc yellow, Hansa yellow, ochre, red iron oxide, and inactive azo dyes. In addition, the organic-inorganic composite resin-containing paint may contain cerium oxide as an inorganic ultraviolet absorber.
[0071] The undercoat layer 32 contains, for example, an acrylic resin. In this case, the weather resistance of the coating film construction 1 can be improved. The undercoat layer 32 is formed by applying a coating agent for forming the undercoat layer 32. For example, an acrylic emulsion paint is used as the coating agent, and it can contain an acrylic emulsion resin, an acrylic silicone emulsion resin, or the like. By forming the undercoat layer 32 from such an acrylic emulsion paint, it is possible to improve the adhesion between the undercoat layer 32 and the topcoat layer 31 formed thereon.
[0072] The photocatalytic activity of the photocatalytic layer 2 can be increased by shortening the time from when the topcoat layer 31 is produced until the photocatalytic layer 2 is produced on the topcoat layer 31. This is presumably because the hydrophobicity of the surface of the topcoat layer 31 is appropriately suppressed as the resin contained in the topcoat layer 31 hardens, so that the photocatalytic particles 20 can be efficiently arranged on the topcoat layer 31. Even if the time until the photocatalytic layer 2 is produced on the topcoat layer 31 is long, the area of the photocatalytic layer 2 can be increased by, for example, reducing the size of the droplets of the coating composition (X), so that the decrease in photocatalytic activity can be suppressed.
[0073] 3. Building materials The building material in this embodiment comprises a substrate and a coating film structure 1 laminated in this order. More specifically, the building material comprises a substrate, an undercoat layer 32, a topcoat layer 31, and a photocatalyst layer 2 laminated in this order. The substrate is formed in a plate shape. The substrate is formed of any material such as a ceramic plate (a hardened product of a hydraulic material containing cement), a plastic plate, a wood plate, a metal plate, etc., and is preferably formed of a material that has been conventionally used as a building material. The surface of the substrate may be unevenly formed to improve design.
[0074] 4. Variations The present invention is not limited to the above embodiment. The above embodiment can be modified in various ways depending on the design, etc., as long as the object of the present invention can be achieved. Modifications of the above embodiment are listed below.
[0075] (First Modification) In the above embodiment, the front surface 21 of the photocatalyst layer 2 is the porous surface 25, but is not limited thereto. For example, both the front surface 21 and the back surface 22 of the photocatalyst layer 2 may be the porous surface 25.
[0076] (Second Modification) In the above embodiment, the photocatalyst layer 2 contains the inorganic particles 27. However, this is not limiting. As long as the photocatalytic action of the photocatalyst layer 2 can be adjusted, the photocatalyst layer 2 does not need to contain the inorganic particles 27. In other words, the coating composition (X) used to prepare the photocatalyst layer 2 may contain the inorganic particles 27 as necessary, but is not required to be an essential component.
[0077] (Third Modification) In the above embodiment, the coating layer 3 is composed of two layers, the topcoat layer 31 and the undercoat layer 32, but is not limited thereto. The coating layer 3 may be composed of one layer, or may be composed of three or more layers. In the present invention, the coating layer 3 may contain an organic-inorganic composite. Therefore, when the coating layer 3 is composed of one layer, that layer may contain an organic-inorganic composite, and when it is composed of three or more layers, any of the layers may contain an organic-inorganic composite.
[0078] (Fourth Modification) In the above embodiment, the photocatalyst particles 20 contain titanium oxide particles, but are not limited thereto. The photocatalyst particles 20 can contain at least one selected from the group consisting of cerium oxide particles, zinc oxide particles, tin oxide particles, iron oxide particles, zirconium oxide particles, tungsten oxide particles, chromium oxide particles, molybdenum oxide particles, ruthenium oxide particles, germanium oxide particles, lead oxide particles, cadmium oxide particles, copper oxide particles, vanadium oxide particles, niobium oxide particles, tantalum oxide particles, manganese oxide particles, cobalt oxide particles, rhodium oxide particles, and rhenium oxide particles, in addition to titanium oxide particles.
[0079] (Fifth Modification) In the above embodiment, the inorganic particles 27 contain silica, but are not limited thereto. The inorganic particles 27 can contain, in addition to silica, a metal oxide containing at least one element selected from the group consisting of titanium, aluminum, zirconium, tantalum, and the like.
[0080] (Sixth Modification) In the above embodiment, the coating composition (X) is applied by spray coating, but the present invention is not limited thereto. In addition to the spray coating, the coating composition (X) can be applied by roll coating, flow coating, shower and air cutting, etc.
[0081] (Seventh Modification) In the above embodiment, the photocatalyst layer 2 contains the binder 24, the photocatalyst particles 20, and the inorganic particles 27, but may contain other components as necessary. Specifically, the photocatalyst layer 2 may contain at least one selected from the group consisting of an ultraviolet absorber and a light stabilizer, in addition to the binder 24, the photocatalyst particles 20, and the inorganic particles 27. The ultraviolet absorber contains at least one selected from the group consisting of, for example, a benzophenone-based ultraviolet absorber, a benzotriazole ultraviolet absorber, and a triazine-based ultraviolet absorber. The light stabilizer contains at least one selected from the group consisting of a hindered amine-based light stabilizer.
[0082] (Eighth Modification) The coating film construction 1 is preferably used for producing building materials, but the application of the coating film construction 1 is not limited to producing building materials. In other words, the coating film construction 1 can be applied to various applications. EXAMPLES
[0083] The present invention will be described in detail below with reference to examples. The present invention is not limited to the following examples, and can be carried out with appropriate modifications, all of which are within the technical scope of the present invention.
[0084] [Preparation of evaluation samples] Example 1 · Acrylic emulsion paint for forming the undercoat layer An acrylic emulsion paint for forming a primer layer was prepared according to the following method.
[0085] <How to prepare acrylic emulsion paint> While stirring 80 parts by mass of acrylic emulsion resin (Dainippon Toryo Co., Ltd.), 2 parts by mass of film-forming aid (2,2,4-trimethyl-1,3-pentanediol monoisobutyrate), 5 parts by mass of thickener (product name Primal ASE-60, Rohm and Haas Japan Co., Ltd.) and 0.1 parts by mass of defoamer (product name Formaster VL, San Nopco Ltd.) were added and stirred for 30 minutes to prepare an acrylic emulsion paint.
[0086] - Organic-inorganic composite resin-containing paint for forming top coat An organic / inorganic composite resin-containing paint for forming a topcoat layer was prepared according to the following method.
[0087] <Method for preparing paint containing organic / inorganic composite resin> In a reactor equipped with a reflux condenser and a stirrer, 23 parts by mass of a partial hydrolysis condensate of methyltrimethoxysilane, 8 parts by mass of methyltrimethoxysilane, 1.7 parts by mass of dimethyldimethoxysilane, 25 parts by mass of a silyl group-containing vinyl resin solution, and 10 parts by mass of isopropanol were added and mixed, and then 3 parts by mass of water and 0.05 parts by mass of 1N hydrochloric acid were added and reacted at 60°C for 3 hours. Next, 0.3 parts by mass of aluminum monoacetylacetonate bis(ethylacetoacetate) and 0.8 parts by mass of water were added, and the mixture was further reacted at 60°C for 3 hours. Next, 0.55 parts by mass of dimethylaminoethanol and 37 parts by mass of water were added, and the mixture was stirred at 50°C for 1 hour, and then the mixture was stirred under reduced pressure (1.3×10 4 After removing the solvent under 200 MPa (Pa), the mixture was diluted with water to a solids concentration of 35% to prepare an aqueous dispersion.
[0088] To 100 parts by mass of the aqueous dispersion obtained above, 12 parts by mass of titanium oxide and 18 parts by mass of carbon black were added. Just before painting, 1 part by mass of an amino group-containing alkoxysilane compound and 2.4 parts by mass of an epoxy group-containing alkoxysilane compound were mixed to prepare an organic-inorganic composite resin-containing paint.
[0089] The silyl group-containing vinyl polymer was synthesized as follows.
[0090] <Preparation of silyl group-containing vinyl resin solution> In a reactor equipped with a reflux condenser and a stirrer, 50 parts by mass of diethylene glycol monobutyl ether and 50 parts by mass of n-butanol were added and heated to 100°C while stirring. Next, a mixed solution consisting of 50 parts by mass of isobutyl methacrylate, 31.5 parts by mass of 2-ethylhexyl methacrylate, 8.5 parts by mass of γ-methacryloxypropyltrimethoxysilane, 10.5 parts by mass of acrylic acid, and 2.5 parts by mass of t-butylperoxy-2-ethylhexanoate was dropped at 100°C over 3 hours, and then the temperature was raised to 105°C and maintained for 2 hours to terminate the reaction. The obtained silyl group-containing vinyl resin solution had a solid concentration of 50%, an acid value of the resin of 65 mgKOH / g, and a number average molecular weight of 10,000.
[0091] Coating composition for forming a photocatalyst layer A coating composition for forming a photocatalyst layer was prepared according to the following method.
[0092] <Method of preparing coating composition> A liquid was obtained by adding 32.5 parts by mass of chain silica (product name: Snowtex OUP, manufactured by Nissan Chemical Co., Ltd.), 32.5 parts by mass of spherical silica (product name: Snowtex O, manufactured by Nissan Chemical Co., Ltd.), and 35 parts by mass of rutile-type titanium oxide (product name: rutile-type titanium oxide sol, manufactured by Teika Co., Ltd.) and stirring the liquid, and 15 parts by mass of a siloxane-based resin (product name: MKC silicate resin, manufactured by Mitsubishi Chemical Co., Ltd.) with a solid content of 20% by mass was added and gently stirred in a thermostatic bath at 20°C for 5 to 15 minutes. Furthermore, 1900 parts by mass of water was mixed and stirred to prepare a coating composition with an NV value of 1.0%. The NV value is also called the heating residue and is a numerical value expressed by (mass after drying the coating composition) / (mass before drying the coating composition)×100.
[0093] - Method for forming coating composition The surface of a ceramic substrate made of cement (hereinafter referred to as substrate) was preheated to 60 to 100° C. Next, the above acrylic emulsion paint was applied using a flow coater, and dried in a jet oven dryer for about 20 to 180 seconds.
[0094] Next, the above organic-inorganic composite resin paint was applied on the undercoat layer using a flow coater and dried in a jet oven dryer.Then, the temperature was raised to 60°C at a heating rate of 20°C / h, and the temperature was kept at this state for 5 hours, and then cooled to room temperature to form a topcoat layer.
[0095] Next, the above-mentioned coating composition for photocatalyst layer was sprayed on the topcoat layer by air spray, and dried at 90°C for 5 minutes to form a photocatalyst layer with a thickness of 0.2 μm. In Example 1, the pressure when the coating composition was applied by air spray was 0.30 MPa, and the particle size of the applied coating composition was adjusted to less than 1 mm. In Example 1, the period from the preparation of the topcoat layer to the formation of the photocatalyst layer was 4 months.
[0096] According to the above procedure, a coating film structure was formed on a substrate, and a building material including the substrate and the coating film structure was produced. In addition, when confirming and evaluating the structure of the photocatalyst layer described below, the building material was cut into a size of 7 cm wide, 15 cm long, and 0.5 cm thick to prepare an evaluation sample.
[0097] Example 2 Compared with Example 1, the inorganic pigment used in the organic-inorganic composite resin coating was changed to 24 parts by mass of carbon black without using titanium oxide.
[0098] Compared with Example 1, in the method of applying the coating agent for the photocatalyst layer, the pressure when applying with an air spray was set to 0.1 MPa, and the particle size of the coating composition when applied was adjusted to 1 mm or less.
[0099] Compared to Example 1, the period from preparation of the topcoat layer to formation of the photocatalyst layer was changed to one month.
[0100] Example 3 Compared to Example 1, the inorganic pigments used in the organic-inorganic composite resin paint were changed so that titanium oxide was not used, the proportion of carbon black was changed to 3 parts by mass, the proportion of pearl mica was changed to 75 parts by mass, and the proportion of cerium oxide was changed to 35 parts by mass.
[0101] In comparison with Example 1, the coating composition was applied using an air spray at a pressure of 0.05 MPa, and the particle size of the coating composition was adjusted to 2 mm or less during application.
[0102] Compared with Example 1, the period from preparation of the topcoat layer to formation of the photocatalyst layer was changed to 5 days.
[0103] Example 4 Compared to Example 1, the inorganic pigments used in the organic-inorganic composite resin paint were changed so that titanium oxide was not used, the proportion of carbon black was changed to 3 parts by mass, the proportion of pearl mica was changed to 75 parts by mass, and the proportion of cerium oxide was changed to 35 parts by mass.
[0104] In comparison with Example 1, the coating composition was applied using an air spray at a pressure of 0.1 MPa, and the particle size of the coating composition was adjusted to 1 mm or less when applied.
[0105] Compared to Example 1, the period from preparation of the topcoat layer to formation of the photocatalyst layer was changed to one month.
[0106] Example 5 Compared with Example 1, the coating composition did not use spherical silica, and the proportion of chain silica was changed to 65 parts by mass.
[0107] Compared with Example 1, the NV value of the coating composition was changed to 0.7%.
[0108] In comparison with Example 1, the coating composition was applied using an air spray at a pressure of 0.05 MPa, and the particle size of the coating composition was adjusted to 2 mm or less during application.
[0109] Comparative Example 1 Compared with Example 1, the coating composition did not use chain silica, and the proportion of spherical silica was changed to 65 parts by mass.
[0110] In comparison with Example 1, the coating composition was applied using an air spray at a pressure of 0.05 MPa, and the particle size of the coating composition was adjusted to 2 mm or less during application.
[0111] Comparative Example 2 Compared to Example 1, the inorganic pigments used in the organic-inorganic composite resin paint were changed so that titanium oxide was not used, the proportion of carbon black was changed to 3 parts by mass, the proportion of pearl mica was changed to 75 parts by mass, and the proportion of cerium oxide was changed to 35 parts by mass.
[0112] In comparison with Example 1, the coating composition was applied using an air spray at a pressure of 0.05 MPa, and the particle size of the coating composition was adjusted to 2 mm or less during application.
[0113] Compared to Example 1, the period from preparation of the topcoat layer to formation of the photocatalyst layer was changed to one month.
[0114] Comparative Example 3 In comparison with Example 1, the coating composition was applied using an air spray at a pressure of 0.05 MPa, and the particle size of the coating composition was adjusted to 2 mm or less during application.
[0115] Compared with Example 1, the NV value of the coating composition was changed to 0.7%.
[0116] Comparative Example 4 Compared with Example 1, the coating composition did not use rutile type titanium oxide particles, the proportion of anatase type titanium oxide particles was changed to 35 parts by mass, and the proportion of spherical silica was changed to 65 parts by mass.
[0117] [Photocatalyst layer structure] <Porous surface> The evaluation sample was further cut out so that the cross section of the coating film structure was exposed, to obtain a slice having a width of 0.5 to 1.0 cm, a length of 0.5 to 1.0 cm, and a thickness of 0.5 to 1.0 cm. The cross section of the coating film structure in the slice was polished by ion milling, and the cross section was observed with a scanning electron microscope (SEM) to obtain a cross-sectional BSE image (composition image). The surface state of the photocatalyst layer reflected in the cross-sectional BSE image of the samples of each example and comparative example was confirmed. The confirmation results were evaluated according to the following criteria and are shown in Tables 1 and 2.
[0118] A: The surface of the photocatalyst layer is porous. B: The surface of the photocatalyst layer is not porous.
[0119] In addition, the cross-sectional SEM image of the sample of Example 1 is shown in FIG. 3, and the cross-sectional SEM image of the sample of Comparative Example 1 is shown in FIG. 4. It was confirmed that the photocatalytic layer of the sample of Example 1 had a porous surface and was also porous inside. On the other hand, it was confirmed that the photocatalytic layer of the sample of Comparative Example 1 had a flat surface and was not porous inside.
[0120] <Surface roughness> Regarding the <presence or absence of a porous surface>, the numerical values (such as the distance from the reference line) used as the basis for calculating Ra were measured for more than 3 screens from the cross-sectional BSE images obtained, and each Ra was calculated. The average value was taken as the surface roughness.
[0121] <Porosity> Regarding the <presence or absence of a porous surface>, image analysis of the cross-sectional BSE images obtained was performed. In the SEM composite image, the ratio of the area of the darkest part corresponding to voids was measured for more than 3 screens, and the average value was taken as the porosity.
[0122] [Evaluation items] [Antifouling property] [Self-cleaning] For the samples, a wet decomposition performance test was carried out in accordance with JIS R 1703-2, and the methylene blue (MB) decomposition activity index was determined from the absorbance at a wavelength of 664 nm. For the measurement of absorbance, an ultraviolet-visible spectrophotometer (product name: V-550, manufactured by JASCO Corporation) was used. The results of the MB decomposition activity index are shown in Tables 1 and 2 according to the following criteria.
[0123] A: MB decomposition activity index exceeds 5 B: MB decomposition activity index is 5 or less
[0124] [NOx removal performance] The NOx removal performance of the samples was evaluated using a chemiluminescence NOx analyzer equipped with a NOx inflow means and an ultraviolet irradiation means. The evaluation was carried out under the conditions of NO supply concentration: 1 ppm, NO flow rate: 1.5 L / min, and ultraviolet irradiance: 6 W / m 2 . The results of the NOx removal performance are shown in Tables 1 and 2 according to the following criteria.
[0125] A: NOx removal is over 0.5 μmol B: NOx removal amount is 0.5μmol or less, 0.4μmol or more C: NOx removal amount is 0.4μmol or less
[0126] (weather resistance) <Exposure to warm areas> In Okinawa Prefecture, the building materials of each Example and Comparative Example were installed facing south at an angle of 20° and exposed for one or two years. The color difference (ΔE) was measured using a colorimeter "CR-400" manufactured by Konica Minolta Holdings, Inc. The results of weather resistance are shown in Tables 1 and 2 according to the following criteria.
[0127] A: ΔE is less than 3 B: ΔE is 3 or more and less than 6 C: ΔE is 6 or more
[0128] [Table 1]
[0129] [Table 2]
[0130] [Aspects] As is apparent from the above-described embodiment, the present invention includes the following aspects.
[0131] The coating film construction 1 according to the first embodiment includes a photocatalyst layer 2 containing a binder 24 and photocatalyst particles 20 dispersed in the binder 24. One of two surfaces of the photocatalyst layer 2 facing opposite directions is a porous surface 25 having a plurality of pores 251 communicating with the outside of the photocatalyst layer 2.
[0132] According to this embodiment, the photocatalytic action of the photocatalyst layer 2 can be efficiently exerted.
[0133] The coating structure 1 according to the second embodiment is the first embodiment, in which the roughness of the porous surface 25 of the photocatalyst layer 2 is 10 nm or more and 100 nm or less.
[0134] According to this embodiment, it is possible to appropriately increase the surface area of the porous surface 25 of the photocatalyst layer 2. This makes it possible to increase the number of photocatalyst particles 20 whose catalytic activity is enhanced when the photocatalyst layer 2 is irradiated with light.
[0135] In the coating film construction 1 according to the third aspect, in the first or second aspect, the photocatalyst layer 2 further contains inorganic particles 27.
[0136] According to this embodiment, the photocatalytic activity of the photocatalyst layer 2 can be adjusted.
[0137] The coating film construction 1 according to the fourth embodiment is produced by applying a coating composition containing a binder raw material, photocatalyst particles 20, and inorganic particles 27 to the photocatalyst layer 2 in the third embodiment. The inorganic particles 27 contain at least one of chain particles and ring particles.
[0138] According to this embodiment, the photocatalyst particles 20 with enhanced catalytic activity can be further increased.
[0139] The coating structure 1 according to the fifth aspect is any one of the first to fourth aspects, in which the photocatalyst layer 2 has a concentration gradient such that the concentration of the photocatalyst particles 20 decreases with increasing distance from the porous surface 25.
[0140] According to this embodiment, the photocatalytic action of the photocatalyst layer 2 disposed at a location farther away from the porous surface 25 can be suppressed.
[0141] The coating structure 1 according to the sixth aspect is any one of the third to fifth aspects, in which the mass ratio of the photocatalyst particles 20 to the inorganic particles 27 in the photocatalyst layer 2 is within the range of 20:80 to 50:50.
[0142] According to this embodiment, the photocatalytic activity of the photocatalyst layer 2 can be easily adjusted.
[0143] The coating film construction 1 according to a seventh aspect is any one of the first to sixth aspects, further comprising a coating film layer 3. The coating film layer 3 contains an organic-inorganic composite. The photocatalyst layer 2 is disposed on the coating film layer 3.
[0144] The coating structure 1 according to an eighth aspect is any one of the first to seventh aspects, in which the photocatalyst particles 20 contain rutile titanium oxide particles.
[0145] According to this embodiment, it is possible to appropriately suppress the photocatalytic activity of the photocatalytic layer 2. This makes it possible to maintain the photocatalytic activity of the photocatalytic layer 2, and also to suppress activity at locations farther away from the porous surface 25.
[0146] The coating composition (X) according to the ninth embodiment contains a binder raw material, photocatalyst particles 20, and inorganic particles 27. The inorganic particles 27 contain at least one of chain particles and ring particles.
[0147] A building material according to a tenth aspect comprises a substrate and the coating film structure 1 according to any one of the first to eighth aspects. [Explanation of symbols]
[0148] 1. Coating film composition 2 Photocatalyst layer 3 Coating layer 20 Photocatalyst particles 24 Binder 25 Porous surface 27 Inorganic particles 31 Top coat layer 32 Undercoat layer 251 Pore
Claims
1. A photocatalyst layer containing a binder and photocatalyst particles dispersed in the binder, One of the two surfaces of the photocatalyst layer facing opposite directions is a porous surface having a plurality of pores communicating with the outside of the photocatalyst layer. Coating film composition.
2. The roughness of the porous surface of the photocatalyst layer is 10 nm or more and 100 nm or less. The coating construction according to claim 1.
3. The photocatalyst layer further contains inorganic particles. The coating construction according to claim 1.
4. The photocatalyst layer is produced by applying a coating composition containing a binder raw material, the photocatalyst particles, and the inorganic particles, The inorganic particles contain at least one of chain particles and ring particles. The coating construction according to claim 3.
5. The photocatalyst layer has a concentration gradient such that the concentration of the photocatalyst particles decreases with increasing distance from the porous surface. The coating construction according to claim 1.
6. The mass ratio of the photocatalyst particles to the inorganic particles in the photocatalyst layer is within a range of 20:80 to 50:
50. The coating construction according to claim 3.
7. Further comprising a coating layer, The coating layer contains an organic-inorganic composite, The photocatalyst layer is disposed on the coating layer. The coating construction according to claim 1.
8. The photocatalyst particles contain rutile titanium oxide particles. The coating construction according to claim 1.
9. Contains a binder raw material, photocatalyst particles, and inorganic particles, The inorganic particles contain at least one of chain particles and ring particles. Coating composition.
10. A coating composition comprising a substrate and the coating composition according to any one of claims 1 to 8. Building materials.
Citation Information
Patent Citations
Coating composition and structure
JP2005113063A